PENTINGNYA DIGITAL BRANDING BAGI PARA PELAKU UMKM GUNA MENGEMBANGKAN UMKM DI KELURAHAN MEDOKAN SEMAMPIR - Dewi Candra Wulan (EDUPEDIA Publisher, 2023)
The internet has a significant impact on the way we live life today, especially for MSMEs players in managing their business. The expansion of product marketing and the development of branding strategies will benefit greatly from the role of the internet in business operations. Considering that Indonesia is currently being attacked by imported goods and the current condition of digital information, it is easier for imported products to enter. Therefore, MSMEs businesses will greatly benefit from using digital branding tactics in order to win the hearts and attention of their customers. This article uses a qualitative descriptive approach to explain the branding process in detail. Through this community service, by providing training and assistance in creating branding for MSMEs products, it is hoped that this can become a guide for MSMEs actors in developing their business through a branding strategy in the digital world.